Analisis Risiko Operasional Bank XXX dengan Metode Teori Nilai Ekstrim - Anik Djuraidah; Pika Silvianti; Aris Yaman (Program Studi Statistika Unisba, 2011)
Bank in its operations are always exposed to risks that are closely related, because of its position as afinancial intermediary institutions. One of the risks which arise when this is operational risk.Operational risk to be one additional factor that must be measured and taken into account in theminimum capital adequacy, in addition to credit and market risk. There are three approaches forsetting capital charges for operational risk, are Basic Indicator Approach, Standardized Approach andAdvanced Measurement Approach. This research used the Advanced Measurement Approach inparticular the use of Extreme Value Theory (EVT) to measure the bank XXX operational risk, this isbecause the distribution of operational risk data have a tendency panhandle. Extreme valueidentification method used is the Peaks over Threshold (POT) method. The results showed that theamount of funds bank XXX must reserve to cover the possibility of operational risk in the period of2010 amounted to Rp 737,210,874, - at 99.9% confidence level. Backtesting results demonstrate thatviable models to be used as a means of measuring operational risk by 99.9% confidence level, for alltypes of operational risk events.